Rare bird documentation form for Glaucous Gull at Lock and Dam 15, 1981 - Petersen, Peter C.et al (1981)
Rare bird documentation form for two Glaucous Gulls at Lock and Dam 15 in Davenport in Scott County, IA on January 4, 1981. Epson - sheet feed